Standardization Of Traditional Pongek Situjuah Food Recipes - Marhamah, Siti; Elida, Elida; Fridayanti, Lucy; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
The background to this research is that there is no standard pongek situjuah recipe in Nagari Situjuah Gadang because there are still differences in ingredients, spices, measurements used and processing processes. This research aims to standardize the pongek situjuah recipe in Nagari Situjuah Gadang, Lima Puluh Kota Regency. This type of research uses a mixed method between quantitative and qualitative descriptive. Qualitative data collection techniques are observation, interviews, documentation and quantitative data collection techniques are organoleptic test questionnaire format. Qualitative data analysis techniques use three activity streams, namely: data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using the formula (Mx=∑ x / N), data validity, testing the validity of qualitative data, namely: extended participation, diligent observation, and triangulation. Based on the research results, 3 pongek situjuah recipes were obtained. The results of the organoleptic test obtained the highest score by Mrs. Damiar from Jorong Padang Jariang with an average score of 27.8. The standardization of the Pongek Situjuah recipe is carried out by organoleptic tests to obtain good quality Pongek Situjuah including: Pongek Situjuah shape (neat and half-crescent shape with a thickness of 3 cm), color of Pongek Situjuah (dark yellow), aroma of Pongek Situjuah (fragrant blend of spices), texture. pongek situjuah (soft and thick sauce) and pongek situjuah (savory) taste.